Faggot Speaks Again: Collage-Based Interpretive Phenomenological Inquiry Into the Poetics of Homophobia - Machado, Sil (Art/Research International, 2026)
This single case study explores the lived experience of homophobia. Expanding upon a previously published poetic inquiry, the author analyzes six autobiographical poems—each describing personal and vicarious encounters with homophobia—as data. Using an interpretive phenomenological analysis, the author identifies five interrelated themes that suggest that homophobia is: (a) an embodied and interpersonal experience; (b) an experience of being diminished by others' beliefs; (c) an experience of danger and threat; (d) an experience of disconnection and alienation; and (e) a disorienting experience accompanied by attempts to understand what feels senseless. The author then represents each theme visually with hand-crafted collages, which offer symbolic and evocative amplifications of the emotional, intrapersonal, and interpersonal elements of each theme. The findings convey a multimodal, embodied, affectively resonant sense of the experience of homophobia, while demonstrating the emancipatory potential arts-based methodologies offer to raise queer voices and foster healing, knowledge, and change.